Kajian Mutu Selai Lembaran Jambu Biji (Psidium guajava) Akibat Konsentrasi Ekstrak Antosianin Bunga Mawar (Rosa sp) dan Jenis Agen Pembentuk Gel - Fina Innama Listin; Elfi Anis Saati; Rista Anggriani (Universitas Muhammadiyah Malang, 2019)
Guava as one of the agribusiness commodities in the primary agricultural sector has several advantages that make this type of fruit in great demand. Proper and correct processing can increase the shelf life of horticultural products, better flavor values have an impact on the preferences and economic value more than the nutritional value contained in the processed fruit. Red guava is rich in pectin, which is very suitable to be processed into slice jam. Slice jam is the result of modification of semi-solid jam. Slice jam is known as fruit leather. The purpose of this study was to determine the interaction between the concentration of rose extract and the difference of gelling agent to physical and chemical characteristics of the guava slice jam. The research method used was Group Randomized Design (GRD) factorial with 2 factors. The first factor was the concentration of rose extract consisting of 5 levels (0%, 2.5%, 5%, 7.5%, 10%). The second factor was the difference of gelling agent consisting of 2 levels (agar 1.5% and carrageenan 1.5%). Parameters analyzed included total soluble solid (° Brix), acidity (pH), vitamin C content, antioxidant activity, total anthocyanin, texture, color intensity (L, a +, b +) and hedonic test (flavor, taste, Appearance, texture). The results of this study showed that there was an interaction between the addition of rose extract concentration and the difference of gelling agent to dissolved solid (° Brix), vitamin C content, antioxidant activity, total anthocyanin, brightness color intensity (L) and redness (a+) guava slice jam. The best treatment was derived at the treatment of 10% roses extract with carrageenan that had 34.20 ° Brix of total soluble solid almost approach the standard of jam (SNI 01 – 3746 – 2008), 3.26 of pH, 96.56 mg / g of vitamin C, 81.45% of antioxidant power, 20.29 mg / g of level anthocyanin, 1.86 of texture, 3.13 of flavor score (quite like), 3.33 of taste score (quite tasty), 3.93 of appearance score (interesting), 2.77 of texture score (quite elastic).